UNILATERAL TONSIL ENLARGEMENT MIMICKING MALIGNANCY: A CASE REPORT - Marsha, Safira Nadita; Syukrinto, Gustav (Syntax Corporation Indonesia, 2025)
Unilateral Tonsil Enlargement (UTE) can present clinically as a significant challenge in differentiation between benign and malignant processes. The suspicion of malignancy increases in older patients who are symptomatic. The purpose of this study was to show that unilateral tonsillar hypertrophy does not always indicate malignancy. A 51-year-old woman presented with a recurring sore throat, but it has been persistent for the past 1 month. A globus sensation accompanied the complaint. On Ear, Nose, and Throat (ENT) examination, the right tonsil grade was T2 and the left tonsil was T4, hyperemic, with dilated crypts. The patient was referred before with a working diagnosis of unilateral tonsil hypertrophy suspect malignancies, with a planned tracheostomy. The literature search was conducted on PubMed, Cochrane, Scopus using keywords “unilateral tonsil enlargement” and “tonsil hypertrophy” and “tonsil asymmetry” in the last 10 years. Based on the investigation, it was found that tonsillectomy for asymptomatic Unilateral Tonsil Enlargement does not need to be performed immediately. Given that the occurrence of malignancy in asymmetrical tonsils is minimal in the absence of additional risk factors, a period of watchful waiting may be deemed appropriate before considering any surgical intervention. It is recommended to observe for four weeks.